2009
DOI: 10.1098/rspa.2008.0352
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of rational spline-based empirical mode decomposition using a global annual precipitation dataset

Abstract: Empirical mode decomposition (EMD), an adaptive data analysis methodology, has the attractive feature of robustness in the presence of nonlinear and non-stationary time series. Recently, in this journal, Pegram and co-authors Proc. R. Soc. A 464, 1483-1501, proposed a modification to the EMD algorithm whereby rational splines replaced cubic splines in the extrema envelope-fitting procedure. The modification was designed to reduce variance inflation, a feature frequently observed in cubic spline-based EMD com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…It is also applicable to nonlinear and nonstationary processes, because it is based on the local characteristic timescale of the data. Since its development by Hunag (1998), it has been used to analyze and model various geophysical data such as sea level, precipitation, radiation and runoff (e.g., Duffy, 2004;Peel et al, 2009;Kuo et al, 2013;Di et al, 2014). For example, Kuo et al (2013) used the ensemble EMD (EEMD Q1 ), a successor of EMD, to derived regional intensity-duration-frequency (IDF) curve for Edmonton, Canada based on the scaling property of precipitation, and Di et al (2014) used the EEMD in combination with artificial neural network models to develop a hydrological forecasting model of precipitation and runoff.…”
Section: Introductionmentioning
confidence: 99%
“…It is also applicable to nonlinear and nonstationary processes, because it is based on the local characteristic timescale of the data. Since its development by Hunag (1998), it has been used to analyze and model various geophysical data such as sea level, precipitation, radiation and runoff (e.g., Duffy, 2004;Peel et al, 2009;Kuo et al, 2013;Di et al, 2014). For example, Kuo et al (2013) used the ensemble EMD (EEMD Q1 ), a successor of EMD, to derived regional intensity-duration-frequency (IDF) curve for Edmonton, Canada based on the scaling property of precipitation, and Di et al (2014) used the EEMD in combination with artificial neural network models to develop a hydrological forecasting model of precipitation and runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the requirements of purely oscillatory functions, the EMD method was developed by Huang et al [1998]. The HSA and EMD have been applied in the field of hydroclimatology during the last few years [ Xie et al , 2002; Chiew et al , 2005; Huang and Wu , 2008; McMahon et al , 2008; Pegram et al , 2008; Peel et al , 2009; Lee and Ouarda , 2010, 2011]. Barnes [2007] showed that the instantaneous frequency has the disadvantage of not being robust in the presence of noise and fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…The value of 0.2 is employed in the current study. Pegram et al [2008] and Peel et al [2009] advocated employing rational splines instead of cubic splines to improve the end effects and to decrease the number of siftings. In the current study, rational splines are not used mainly because their use requires additional adjusting procedures which are time consuming and need some additional work.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the rational spline method is that it allows for an interplay between spline tension and IMF characteristics, whereas the original cubic method provides a single output [ Pegram et al , 2008]. Peel et al [2009] carried out additional work to assess the performance of rational spline‐based EMD for a global annual precipitation data set. Future research efforts on the use of EMD in the prediction of nonstationary hydroclimatological oscillation processes should integrate the use of rational splines.…”
Section: Introductionmentioning
confidence: 99%